2006
DOI: 10.1351/pac200678061265
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted combustion

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The gas flow is modeled by solving the mass, momentum, and total energy conservation equations simultaneously, as given by Eqs. (4)(5)(6), respectively,…”
Section: B Governing Equations and Initial/boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas flow is modeled by solving the mass, momentum, and total energy conservation equations simultaneously, as given by Eqs. (4)(5)(6), respectively,…”
Section: B Governing Equations and Initial/boundary Conditionsmentioning
confidence: 99%
“…O VER the past few years, nonequilibrium plasma discharges have shown great potential to enhance and stabilize the combustion process in internal combustion engines, gas turbines, and scramjet engines [1][2][3][4]. Experiments have demonstrated that plasmas can shorten ignition delay times [5][6][7][8][9][10][11], extend extinction limits [12,13], improve flame stabilization [12,14], increase flame speed [6,15], and suppress soot formation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…High efficiency of the fast ionization wave for spatially-uniform excitation of the chemicallyreacting systems has been found [Kof&Starikovskiy, 1996-1;1996-2]. The experimental works using this installation show the high efficiency of this methodology for hightemperature plasma assisted combustion investigation (see, for example, [Aleksandrov et al, 2009-1;2009-2;2008-2;Starikovskii et al, 2006;Starikovskaia et al, 2004;Bozhenkov et al, 2003;2002]). The kinetics of ignition in C n H 2n +2O 2 :Ar mixtures for n = 2 to 5 has been studied experimentally and numerically after a high-voltage nanosecond discharge .…”
Section: Plasma Assisted Combustion Above Self-ignition Thresholdmentioning
confidence: 89%
“…As demonstrated by Kim and colleagues [19] and Rosocha and co-workers [20], in such plasmas, electron temperatures lower than 12 eV can break down the fuel species producing free radicals. To date, several DBD-PAs have been investigated to improve the fuel/air mixtures ignition [21][22][23], increase flame propagation [24,25], or enhance flame stabilization by extending flammability limits [26][27][28][29][30][31]. Concerning this last aspect, combustion enhancement has been observed when applying a DBD-PA for fuel/oxidizer decomposition [32,33].…”
Section: Introductionmentioning
confidence: 99%